In vitro immune response of spleen cells from mice genetically selected for high or low antibody production. - Doria, G (1978)
The aim of this study was the identification of the cell type in which genes selected for high or low response to SRBC express their functions. Spleen cells from high (H) and low (L) responder mice were immunized with SRBC in the Mishell and Dutton system. An antibody response of different magnitude was found in cultures of H and L spleen cells, the difference being at least as great as that observed in vivo. This finding under experimental conditions allowing the exclusion of any influence of the animal milieu during the immune response, suggest macrophages, B, and T lymphocytes as possible target cells of gene action. In vitro cell separation and recombination experiments in which spleen cells were immunized with SRBC, TNP-LPS, or TNP-HRBC indicate that the genetic differences between H and L responders brought about by selective breeding are expressed in lymphocytes to greater extent than in macrophages. The role of histoincompatibility in the recombination experiments in unlikely but cannot be excluded. Among lymphocytes, B cells but not helper T cells were found more responsive in cultures of spleen cells from H than from L mice.